Pengembangan Media Ular Tangga Mata Pelajaran Matematika Kelas III Sekolah Dasar - Fadila, Aprilia Sindi; Yuanta, Friendha; Suryarini, Diah Yovita (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
The purpose of this writer is to develop snake ladder imedia in ithe addition iand subtraction material iof grade III students at SD Darul Ulum Surabaya and iis isuitable for use iin ithe ilearning iprocess. The author's design will modify the snakes and ladders game into a learning medium that will be adjusted through teaching materials along with the competencies to be provided. This snake ladder media approach will be centered on students and students will be more active in using learning media. The imethod iused iin this development is the ADDIE learning design model (Analysis, Planning, development, Implementation, and Evaluation). ADDIE model is one model that can guide students to plan the learning process actively. This snake and ladder media only received validation from media and material experts, the writer did not implement it in school because of the covid-19 virus pandemic. By. Therefore, ibased ion ithe iresults iof ithe validation iof this development, a ipercentage iof 80% of media iexperts iwas iincluded iin ithe category of quite feasible and a percentage of 100% of material experts was included in the appropriate icategory so that the snake ladder of mathematics learning material for addition and subtraction of grade III SD Darul Ulum was declared suitable ifor iuse iin learning process.Â Keywords: development of ilearning imedia, ladder isnake imedia, mathematics.Â